THE EMIRATE OF SORAN IN THE ERA OF KHANZADA KHATUN 1617-1661: A STUDY OF THE ADMINISTRATIVE ASPECTS - Hasan, Nazar (Humanities Journal of University of Zakho, 2025)
The 17th century is considered one of the dark periods in the history of the Kurdish Emirates, because there is no such an inclusive book tackling their history. Unlike the book Sharafnameh written by Prince Sharafkhan Badlisi, which covered the history of Kurdistan throughout the 16th century, there is little information that can be found among some Ottoman and Safavid sources. The Emirate of Soran is one of those emirates that may have received the lion's share of neglect and lack of attention, especially during the 17th and 18th centuries. Therefore, the researcher, who writes on the history of the aforementioned emirate, must search through ancient documents, records, and manuscripts in archives, requiring a consuming time and effort. This study examines the history of Soran in one of its most important eras, which was the era of Princess Khanzadeh Khatun, the first woman to hold the position of Sanjakbey in the Ottoman Empire. However, the published and available information about this princess is rare to an extent that some regarded her as a fictional heroine in the Kurdish oral literature. The research paper is divided into two main sections. Section one is devoted to tackle the life of Khanzadeh Khatun and her administrative, political, and military role. Section two examines the four princes of the Sanjaks in Soran, namely: Harir and Dowian, Erbil, Shamamak, and Koya. It is worth noting that most of the information in our study is published for the first time. The study has mainly depended on the Ottoman placement records (also known as the Ruus registers) and the records of directing the timariots (timar), the chieftains (zeamet), and the Sultan orders preserved in the Muhimme Dafteri, the various Ottoman documents, as well as the Safavid and Ottoman sources that dealt with topics from the history of the Emirate of Soran during the reign of the princess Khanzadeh Khatun.